Optimization of Bentonite Bar Soap Formula with Combination of Coconut Oil and Soybean Oil Using Simplex Lattice Design Method - Farah Ataya; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2022)
Muslim population in Indonesia reaches 87% and is one of the countries with the largest muslim population according to the 2010 population census. Thaharah is one of the things that Muslims pay much attention to, especially in worship. One of thaharah is washing up from najis mughallazah. Soap is skin cleansing preparations that has become a public basic needs so that the innovation of soap formulation containing bentonite as a component that can washed the najis mughallazah to make it easier for Muslims to thaharah. This study optimizes the formula for bentonite bar soap with combination of coconut oil and soybean oil using the Simplex Lattice Design method. The optimum formula obtained was then verified using the one sample T-test method. To determine the optimum formula, it is necessary to test the physical and chemical properties such as foaming power and foam stability and follows the parameters of the Standar Nasional Indonesia such as foaming water content, pH, total fat, insoluble substance in ethanol, free alkali/ free fatty acid and unsaponifiable fat. Bentonite soap with the optimum formula was then tested for consumer acceptance. The optimum formula from the prediction consisted of 76.58% coconut oil and 23.42% soybean oil. The test results of the formula produced soap with hard properties and good foaming and met several requirements of SNI 3532:2021.